Studi Peran Kekuatan Perut dalam Meningkatkan Performa Tolak Peluru pada Atlet - Situmorang, Dimas Alfani; Rumahorbo, Johan Agung Adrian; Gultom, Randy Anugerah; Saragi, Zefta Exaudy; -, Nurkadri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the role of abdominal strength in improving shot put performance in athletes. This research uses a literature review method by collecting information by looking for relevant references and facts from journals and theses that have been previously researched. The literature is then compared and linked to provide an overview of the topic under study. Qualitative research is used as a type of research. This research explores the role of abdominal muscle strength in improving shot put performance in athletes. Shot put requires the right combination of strength, technique and coordination to achieve optimal results. One key element that is often overlooked is abdominal muscle strength or core strength. This research outlines how abdominal muscle strength contributes to body stability, efficient energy transfer, and optimization of shot put technique. Through literature analysis and research findings, it was concluded that integrated abdominal strength training in athlete training programs can help improve shot put performance by optimizing stability, energy transfer and movement technique. The practical implication is the importance of including abdominal strength training in the training program to achieve maximum performance in shot put and reduce the risk of injury. Further research could explore more deeply the long-term influence of abdominal strength training on the performance of shot put athletes.